Normotensive patients with obstructive sleep apnoea: changes in 24-h ambulatory blood pressure monitoring with continuous positive airway pressure treatment. Issue 4 (April 2019) - Sapiña-Beltrán, Esther; Santamaria-Martos, Fernando; Benítez, Ivan; Torres, Gerard; Masa, Juan F.; Sánchez-de-la-Torre, Manuel; Barbé, Ferran; Dalmases, Mireia
Abstract : Background: Continuous positive airway pressure (CPAP) treatment reduces blood pressure (BP) in obstructive sleep apnoea (OSA) and hypertensive patients, but there is a lack of data about the effects of CPAP on the BP in normotensive patients. Objective: The aim of the study was to evaluate BP changes in normotensive OSA individuals receiving CPAP treatment. Methods: We selected 131 normotensive outpatients with an apnoea/hypopnoea index (AHI) greater than 15 events/hour who required CPAP treatment. All patients underwent a sleep study and 24-h ambulatory BP monitoring (ABPM) at baseline and after 6 months. In addition, the patients were assessed for the presence of baseline masked hypertension, defined as office BP less than 140/90 mmHg and increased BP on 24-h ABPM (mean 24-h BP ≥130/80 mmHg). Results: After 6 months of CPAP treatment, a mild reduction in all 24-h ABPM variables was observed, but only the mean 24-h DBP [−1.39 mmHg, 95% confidence interval (95% CI), −2.50 to −0.27], mean daytime DBP (−1.39 mmHg, 95% CI −2.56 to −0.22) and the mean 24-h ambulatory BP (−1.80 mmHg, 95% CI, −3.16 to −0.44) reached statistical significance. The reduction was primarily due to BP changes in individuals with masked hypertension who displayed a mean BP reduction of −4.78 mmHg (−7.25 to −2.30 mmHg). Consistent with a circadian BP pattern, a reduction in mean nocturnal BP of −4.73 mmHg (−7.39 to −2.06 mmHg) was observed at 6 months in nondippers; in contrast, the mean nocturnal BP in dippers increased by 2.61 mmHg (0.60–4.62 mmHg). Conclusion: Our findings suggest that the CPAP effects may be different in normotensive outpatients depending on the presence of undiagnosed masked hypertension and the dipping pattern. Therefore, it is important to consider measuring ABPM in this type of patient. Abstract : Supplemental Digital Content is available in the text